PENGARUH PEMBELAJARAN MENGGUNAKAN MODUL TERHADAP HASIL BELAJAR MATA KULIAH TEKNIK PEMESINAN DAN FABRIKASI JURUSAN TEKNIK MESIN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Suparno Suparno; Bulkia Rahim (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2017)
Based on observations, that the problem is: the limited availability of the book and yet Machining and Fabrication Techniques module, causing the learning process is not maximized. The research objective to describe the learning outcomes using the modules on the course Theory Fabrication Engineering Department of Mechanical Engineering, Faculty of Engineering University of Padang and determine the effect of learning by using modules for learning outcomes on the eye Lecture Machining and Fabrication Engineering Department of Mechanical Engineering, Faculty of Engineering, State University of Padang. Subjects were students of Mechanical Engineering FT-UNP who take courses Mechanical Machining and Fabrication. The type of data in this study are primary data obtained directly from students are taken through a questionnaire. Instrument data collectors questionnaire form. Based on the findings of this study concluded that the use of this fabrication technique Theory module effectively to improve learning outcomes, evidenced by higher average results of experimental class learning with classroom control D3 students of Mechanical Engineering are taking courses in Mechanical Fabrication.